Réponses

2013-04-06T17:36:54+02:00

Bonjour,

 

a)Facteur commun : x

a = x (5x-3)

 

b)Facteur commun : (x-1)

B = (x-1)^2 -2(x-1)\\ B = (x-1)\left[(x-1)-2\right]\\ B = (x-1)(x-3)

 

c)

Facteur commun : (2x+1)

C = (2x+1)(3x-4)+5(2x+1)\\ C = (2x+1)\left[(3x-4)+5\right]\\ C = (2x+1)(3x+1)

Meilleure réponse !
2013-04-06T18:07:09+02:00

A = 5x² - 3x                                  ici, le facteur commun est x. donc on l'isole

A = x(5x - 3)

 

B = (x - 1)² - 2(x - 1)                    ici, le facteur commun est (x - 1)

B = (x - 1)(x - 1 - 2)

B = (x - 1)(x - 3)

 

C = (2x + 1)(3x - 4) + 5(2x + 1)                   ici, le facteur commun est (2x + 1)

C = (2x + 1)(3x - 4 + 5)

C = (2x + 1)(3x + 1)